2021
DOI: 10.3892/mco.2021.2304
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization using hydrogen peroxide in patients with cervical cancer

Abstract: The purpose of the present study was to analyze the feasibility and safety of radiosensitization using hydrogen peroxide for cervical cancer. In superficial tumors, breast cancer and hepatocellular carcinoma, the safety and effectiveness of radiosensitization has been reported; to the best of our knowledge, however, there are no reports on cervical cancer. A total of 20 patients with cervical cancer were recruited. Inclusion criteria were as follows: Patients who required radical external beam radiotherapy (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Radiosensitizers, on the other hand, are agents that enhance the therapeutic ratio of radiation therapy by enhancing DNA damage, free-radical production, or both when combined with radiation, while not damaging the normal cells in the process. A few potential clinical radiosensitizers are currently being used in patient trials [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], in the context of a historic backdrop of many others, ultimately resulting in limited clinical efficacy and increased toxicity to normal tissues [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiosensitizers, on the other hand, are agents that enhance the therapeutic ratio of radiation therapy by enhancing DNA damage, free-radical production, or both when combined with radiation, while not damaging the normal cells in the process. A few potential clinical radiosensitizers are currently being used in patient trials [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], in the context of a historic backdrop of many others, ultimately resulting in limited clinical efficacy and increased toxicity to normal tissues [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study from our institution showed the feasibility and safety of radiosensitization using hydrogen peroxide for patients with cervical cancer who are ineligible for brachytherapy ( 17 ). Briefly, 18 patients received treatment comprising a 3% hydrogen peroxide solution-soaked gauze inserted into the vagina during RT twice a week.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hydrogen peroxide was used twice a week in combination with RT. Because the anticipated potential risk of this radiosensitization was adverse effects on the mucosal tissue surrounding the tumor, we referred to the method of radiosensitization used in patient with cervical cancer, which was reported in the literature ( 17 ). Here 3% hydrogen peroxide solution-soaked gauze was inserted into the vagina during RT twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…One stratagem is to use oxygen-mimicking compounds which have been shown as potent radiosensitizers for several cancers. It has also been shown that some molecules which can carry oxygen such as hydrogen peroxide or nitric acid can be used as radiosensitizers [49,50].…”
Section: Application Of Nanodrugs As Radiosensitizers For Gbm Therapymentioning
confidence: 99%